FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN KONTRASEPSI PADA WANITA DENGAN PERNIKAHAN USIA DINI - Simanjuntak, Herlina; Maynia, Fika Ayu (Asosiasi Pendidikan Kebidanan Indonesia, 2018)
The proportion of the use of KB (family planning program) by early marriage women  is low . The aimed of this studi is to identify related factors to contraception use among  early marriage women in Banjarsari village, district of Sukatani, Bekasi regency. A cross sectional study was done involving 53 women with early marriage, sampling by total sampling. The subject which sample criteria were interviewed using questionnaires to obtain data of the use of contaception, knowledge, education level, occupation, support of husband and information sources. The data were analyzed in both univariate and bivariate using chi square test. The findings show that most of contraceptive users were women with early marriage knowledgeable (86.2%) with p value of 0.001, experiencing higher education (76.9%) with p value of 0,004, supported by husband (92.9%) with p value of 0.000 and getting information from health workers (87.2%) with p value of 0.000. The conclusion of this study show that knowledge, education level, support of husband and sources of information are factors relating to the use of contraception among early marriage women.